Men who hate women : from incels to pickup artists, the truth about extreme misogyny and how it affects us all / Laura Bates. - Bates, Laura, 1986- (Simon & Schuster, 2021)
This is an explosive book examining the rise of secretive, extremist communities who despise women. In this ground-breaking investigation, Laura traces the roots of misogyny across a complex spiders web of groups extending from Men's Rights Activists and Pick up Artists to Men Going their Own Way, Trolls and the Incel movement, in the name of which some men have committed terrorist acts. Drawing parallels with other extremist movements around the world, Bates seeks to understand what attracts men to the movement, how it grooms and radicalises boys, how it operates and what can be done to stop it. Most urgently of all, she traces the pathways this extreme ideology has taken from the darkest corners of the Internet to emerge covertly in our mainstream media, our playgrounds, and our parliament.